Mobilitas Pengunjung di Kawasan Wisata Perkotaan Pakuwon City Surabaya - Adinda Sanita Putri Khinari; Ida Bagus Suryawan (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2021)
Surabaya is the capital of East Java Province as well as the center of the Gerbangkertosusila megacities. Surabaya as an urban area with various functions has resulted in urban tourism, one of which is Pakuwon City. Pakuwon City, which is a residential area with various facilities that can be used in general, is also the main attraction for visitors to carry out various tourist activities in Pakuwon City.This research uses quantitative method. The sources of data in this research were compiled based on quantitative and qualitative data types using primary data in the form of observations and questionnaires, as well as secondary data obtained through literature study. The sample used was 37 respondents obtained through accidental sampling from visitors who had visited Pakuwon City. The data obtained were analyzed using descriptive, frequency distribution, and spatial models.The result of this research is that Pakuwon City has three pull factors which include high density, concentrating on commercial, financial, industrial and hospital activities, as well as providing artistic and recreational experiences. Eight tourist attractions in Pakuwon City are classified based on their main function as factors that attract visitors to visit Pakuwon City. This pull factor causes the movement of visitors which is dominated by the movement to the tourist attraction Pakuwon Town Square with many activities carried out, namely shopping. Keyword: Pakuwon City, urban tourism pull factor, mobilities